If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + -3 = 5(y + -1) Reorder the terms: -3 + 5y = 5(y + -1) Reorder the terms: -3 + 5y = 5(-1 + y) -3 + 5y = (-1 * 5 + y * 5) -3 + 5y = (-5 + 5y) Add '-5y' to each side of the equation. -3 + 5y + -5y = -5 + 5y + -5y Combine like terms: 5y + -5y = 0 -3 + 0 = -5 + 5y + -5y -3 = -5 + 5y + -5y Combine like terms: 5y + -5y = 0 -3 = -5 + 0 -3 = -5 Solving -3 = -5 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 2x+3=2y | | 6t=48 | | x-2x=3x-27 | | -4(8+5)=8 | | 7k=k-18 | | 49x=245 | | y=-20sin(4x) | | -3y-10=6y+17 | | -10v+2=-70 | | 2x-2y=3 | | 3x-15=90 | | 4z+20=24 | | -4(x-5)+6=26 | | 4n+8=48 | | w+6=2w-3 | | n+1=2 | | 10x+7=11x-1 | | -16x^2-48x-32=0 | | 3+x=-12+8 | | 144f^2-24f+1=0 | | 17x+4=19x-4 | | -42x^2+84x-42=0 | | 20x-5=9+13x | | 22x+2=19x-4 | | -(-49-2b)-(3b+6)= | | 22x+2+19x-4=90 | | 16x-12=17x | | 18=4y | | 5+6q=9+5q | | -11(4k+6)=198 | | .66x+92=-31 | | 8x-9=7x-7 |